TINGKAT KESIAPAN IBU NIFAS DENGAN ADAPTASI NEW NORMAL PENCEGAHAN PANDEMI COVID 19 DI RS. BHAYANGKARA MANADO - Goldy, Hana; Ake, Julianus; Polii, Grace (Fakultas Keperawatan, Universitas Katolik De La Salle Manado, 2022)
Introduction: The Covid-19 pandemic affects the readiness level of postpartum mothers in entering the new normal adaptation.The Covid-19 outbreak has resulted in many reductions in general activities, both in access and quality, and a reduction in maternal health services. Objective: To know the relationship between the readiness level of postpartum mothers and the new normal adaptation of Covid-19 prevention at Bhayangkara Hospital Manado. Method: This research is a quantitative research that used the cross-sectional research design. The location of this research was Bhayangkara Manado Hospital. The population size for this survey was 43 respondents, the number of samples was 43, obtained using a non-probability sampling technique, consecutive sampling method. This study used the Spearman correlation test and data collectionusing a questionnaire sheet. Results: The results showed that the respondents' readiness for postpartum mothers were high (93.3%) in facing the new normal adaptation and respondents with high new normal adaptation (67.4%). The results of the bivariate analysis using the Spearman correlation test showed the value of p = 0.006. Conclusion: There was a significant effect between the level of readiness of postpartum mothers and the new normal adaptation of the Covid-19 pandemic prevention.